MHD flow due to stretching sheet embedded in non Darcian porous medium with thermal stratification effects (Journal of Naval Architecture and Marine Engineering, 2018)
The aim of present study is to analyze the non- Darcian effects on unsteady non-linear MHD flow of an incompressible, electrically conducting and viscous fluid over a stretching sheet embedded in a porous medium with heat source, viscous dissipation and thermal stratification. The dimensionless governing equation solved numerically by using 4th order Runge - Kutta method. The effects of pertinent parameters on velocity and temperature depicted graphically.